Risks and Benefits of Private Health Care: Exploring Physicians’ Attitudes Towards the Privatisation Of Health Care in Malaysia - Hawdon, Christine (2009)
Health care has become a political issue in Malaysia. Unlike many countries where there is an established health care system, the role of the Malaysian government in the provision of health care services is questioned by the people who use it, the people who provide it, and moreover the government itself. Confusion over whether heath care should be a public or private service has led to the emergence of a ‘dual’ system whereby public services operate, perhaps compete, against private services. Since the 1980s though, there has been an increasing trend towards the privatisation of health care. This has been met with political contention from the public sector and those who support it, who see health care not as a service to be consumed by those who can afford it, but by all those who need it. Consequently the decision over who should provide health care is under great contest in Malaysia’s political, social and economic spheres. This study attempts to look at why this confusion has occurred – is it a result of Malaysia’s ‘failure’ to ever set up a succinct, satisfactory public health service, or is it a result of conflicting political interests which have emerged from Malaysia’s turbulent yet rapid transition from a less economically developed country to one of South East Asia’s most successful economies? This study also explores physicians’ views about the obvious turmoil in Malaysia’s health care system. Physicians are, after all, the most important contributors to health care services everywhere. As such, this study will be the first of its kind in Malaysia, interviewing physicians as to their views on privatisation, their views on the motivations for this, and their views on the fact that their profession has become a political issue leaving them with little choice but to follow the trend or leave the health care sector altogether.